Micro/nanostructuring of metal additively manufactured aluminum alloy for enhanced pool boiling of dielectric fluids - Lum, Leymus Yong Xiang (2024)
Surface micro/nanotextures have the potential to increase bubble nucleation and promote capillary liquid wicking to enhance pool boiling heat transfer significantly. Despite past studies implementing surface micro/nanofabrication strategies to enhance boiling, the role of structure length scale and morphology on boiling heat transfer coefficient (h) and critical heat flux (CHF) of low-surface-tension dielectric fluids remains unclear. In this study, we systematically tune the surface microstructures on additively and conventionally manufactured aluminum alloys (AM AlSi10Mg and Al6061) from 1 µm to 5 µm to study the influence of microstructure length scale on boiling performance. In addition, to further understand the effect of submicron structures on boiling, nanostructures of 300 nm length were generated on a plain AM surface and hierarchically incorporated atop the microstructures. Dielectric fluid, HFE-7100, was used to investigate the effects of surface morphology on pool boiling heat transfer coefficient (h) and critical heat flux (CHF). Our results show that the 5 µm microstructured AM surface, AM-H(400)E(5), attained a CHF of 19.44 W/cm2 and a maximum heat transfer coefficient (hmax) of 2.89 W/cm2·K, which represents a reduction in CHF of 28.5 % and an enhancement in hmax of 103.8 %, as compared to the plain Al6061 surface. In addition, AM-H(400)E(5) achieved a large enhancement ratio of 2.2 as compared to the plain Al6061 at a heat flux of 20 W/cm2, and the highest h value amongst all structured surfaces, indicating its cavity size is optimal for bubble nucleation. Through the systematic tuning of micro/nanostructures length scale and morphology, this study found that the micro/nanostructures of 1 µm size and below are too small to serve as bubble nucleation sites. Additionally, micro/nanostructure wickability plays a negligible role in affecting pool boiling performances of highly wetting dielectric fluids, while surface morphology plays a dominant role in bubble nucleation to enhance boiling. Lastly, high-speed immersion microscopy was performed to understand the effects of micro/nanostructures on bubble characteristics such as bubble departure diameter and growth period. In summary, this work not only reports the first micro/nanostructured AM surfaces utilizing scalable fabrication techniques for enhanced boiling, but it also demonstrates the potential of tunning the micro/nanostructure length scale to optimize the bubble nucleation site density, resulting in significantly improved pool boiling performances.